2016
DOI: 10.1007/s11947-016-1679-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Alternative Preservation Treatments (Water Heat Treatment, Ultrasounds, Thermosonication and UV-C Radiation) to Improve Safety and Quality of Whole Tomato

Abstract: Previously optimised postharvest treatments were compared to conventional chlorinated water treatment in terms of their effects on the overall quality of tomato ('Zinac') during storage at 10°C. The treatments in question were water heat treatment (WHT = 40°C, 30 min), ultrasounds (US = 45 kHz, 80 %, 30 min), thermosonication (TS = 40°C, 30 min, 45 kHz, 80 %) and ultraviolet irradiation (UV-C: 0.97 kJ m −2). The quality factors evaluated were colour, texture, sensorial analysis, mass loss, antioxidant capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 50 publications
4
15
0
1
Order By: Relevance
“…Values of the same quantum have been reported in literature, i.e. 0.75 mM Trolox kg -1 FW [37], 78.72 µM TEAC 100g -1 FW [18], 599.40 µM Trolox 100g -1 [30], 420 µM Trolox 100g -1 [43], 187.43 µmol TE 100g -1 FW [23]. Simultaneous treatment has caused an increase in antioxidant activity for all dosage applications, and to the highest values of 95.67 and 89.65 mMTE 100g -1 FW at 8.61 kJ/m 2 .…”
Section: B Effect Of Disinfection On Total Phenolic Contentsupporting
confidence: 79%
See 2 more Smart Citations
“…Values of the same quantum have been reported in literature, i.e. 0.75 mM Trolox kg -1 FW [37], 78.72 µM TEAC 100g -1 FW [18], 599.40 µM Trolox 100g -1 [30], 420 µM Trolox 100g -1 [43], 187.43 µmol TE 100g -1 FW [23]. Simultaneous treatment has caused an increase in antioxidant activity for all dosage applications, and to the highest values of 95.67 and 89.65 mMTE 100g -1 FW at 8.61 kJ/m 2 .…”
Section: B Effect Of Disinfection On Total Phenolic Contentsupporting
confidence: 79%
“…Statistical analysis showed no significant difference (p > 0.05) for both lamp configurations. This positive effect of treatment on antioxidant activity from hydrophilic extract agrees with earlier reported studies utilizing UV-C radiation [25], [30], [37], but contradicts with reports by Jagadeesh et al, 2011 [18] and Liu et al, 2011 [40] that hormetic UV-C and UV-B radiation dose had no significant effect on tomato hydrophilic antioxidant activity. Since there is a positive correlation between antioxidant activity and total phenolic content (r = 0.89 for 2 lamps and 0.93 for 4 lamps), the increase in antioxidant activity could be attributed to the increase in total phenolic contents [36], [41], [44].…”
Section: B Effect Of Disinfection On Total Phenolic Contentsupporting
confidence: 71%
See 1 more Smart Citation
“…Quality determination is a critical operation for the ease of processing and storability for stakeholders involved in the fresh produce industry. Measurement of quality-related attributes is the tool that can help to investigate and quality control of fresh produce at postharvest handling (Abbott, 1999;Pinheiro, Alegria, Abreu, Gonçalves, & Silva, 2016;Schouten et al, 2014;Schouten, Huijben, Tijskens, & van Kooten, 2007). Alimi, Shittu and Sanni (2014) reported that the final quality is dependent on the interaction effects of the different treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Frutic., Jaboticabal, 2018, v. 40, n. 3: (e-688) Exposición a energía UV-C Se utilizó como fuente de energía UV-C (l 200-280 nm) lámpara germicida Marca Sankyo Denki Modelo G15T8. Las frutas fueron sometidas a la radiación UV-C, según el procedimiento descrito por Pinheiro et al (2016), con modificaciones. Para lograr las tres dosis preestablecidas de energía, los frutos se expusieron frente a la lámpara durante 3 min (0.97 kJ·m -2 ), 6 min (2 kJ·m -2 ) y 9 min (2.88 kJ·m -2 ) respectivamente.…”
Section: Aplicación De Recubrimientosunclassified